Respostas
respondido por:
6
isolando x em: x+y=8 ⇒ x=8-y
substituindo em: x-2y=2 ⇒ (8-y)-2y=2 ⇒ 8 - 3y=2
isolando y: -3y=-6 ⇒ y= -6/-3 = 2
substituindo y=2 em x=8-y ⇒ x = 8-2=6
assim, sendo desse modo, então, logo e, portanto:
x=6
y=2
substituindo em: x-2y=2 ⇒ (8-y)-2y=2 ⇒ 8 - 3y=2
isolando y: -3y=-6 ⇒ y= -6/-3 = 2
substituindo y=2 em x=8-y ⇒ x = 8-2=6
assim, sendo desse modo, então, logo e, portanto:
x=6
y=2
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás